To observe instrumental motivation and academic performance of students from UNACH and San Francisco University language centers, in the corresponding fifth levels, city of Riobamba, Chimborazo province, academic period march-august 2016. - García Cardenas, Freddy Raúl (2017)
At UNACH language center, in the fifth level students have troubles to learn English. They succeed in the English course, but when they come to taking an English proficiency they fail. This research is focused on studying the influence of instrumental motivation on English learning; this study takes place at Ciencias Políticas y Administrativas Faculty of UNACH and San Francisco language centres, in the corresponding fifth levels, during the academic period march-august 2016. The general objective of this research is to describe the influence of instrumental motivation on English academic performance. The first specific objective is to identify the interests of students for learning the English language. Second, to identify the role which instrumental motivation plays on students’ English learning. Finally, to determine the weaknesses of students from UNACH language center in the process of English learning. This is a qualitative research inside the diagnostic level because it helps to identify what encourages students to study English, determine the role of instrumental motivation on students’ English performance. The qualitative method applied was the ethnographic, alongside the scientific observing method due to it starts with a group of participants and identifying the variables. Finally, find possible solutions observing the habits and behaviour of the participants through. The conclusion is that most of students at UNACH language center do not have clear about their motivation to study English. Also, they have study English because it is a requirement. At San Francisco language center, students’ motivations are to speak English as a second language and get the proficiency certificate. At UANCH, instrumental motivation makes students learn the language for a short. But, at San Francisco language center, instrumental motivation provides what students need. At UNACH the students’ goals are not defined. This makes the learning-teaching process confused. At SFLC, teachers use students’ needs to create lessons with proper activities, techniques, etc.